The macroeconomics of epidemics: Interstate heterogeneity in Brazil - Luan Borelli; Geraldo Sandoval Góes (EconomiA, 2021)
We applied the SIR-macro model proposed by Eichenbaum et al. (2020) in its complete version to comparatively study the interaction between economic decisions and COVID-19 epidemics in five different Brazilian states: S\~ao Paulo (SP), Amazonas (AM), Ceará (CE), Rio de Janeiro (RJ), and Pernambuco (PE). Our goal was to analyze qualitatively how the main intrinsic differences of each of these states could affect the epidemic dynamics and its consequences. We computed and compared the model for each of the states, both in competitive equilibrium and under optimal containment policy adoption, and analyzed the implications of optimal policy adoption. We concluded that the intrinsic characteristics of the five different states could imply relevant differences in the general dynamics of the epidemic, in the optimal containment policies, in the effect of the adoption of these policies, and the severity of the economic recessions. One year after the original ex-ante calibration, we evaluated the death toll and economic recession predicted by the model comparing it against real data. The model predictions showed to be qualitatively sufficient to anticipate the size of the pandemic risk that later materialized in Brazil.
Keywords: E1; I1; H0; 330; Containment policy; COVID-19; Epidemics; Recessions; SIR-macro model; States